Створення програмного забезпечення мотиваційної функції управління людським капіталом - Цигилик, Юлія (Видавництво Львівської політехніки, 2018)
The modern development of organization in Ukraine is characterized by a number of features, which is connected with global economy. In the western regions, which are geographically close to the border with the EU, an enterprise has an additional motivation effect. The emergence of new functions requires detailed analysis. This can be traced also in terms of IT sector of Lviv region.
Keywords: людський капітал; мотивація; методика; програмне забезпечення